The effect of a malfunctioning braking system on the behaviour of a special vehicle during an emergency braking in a curvilinear movement - Simiński , Przemysław; Neumann, Vlastimil; Svoboda, Pavel; Cibulová, Klára; Vnuk, Radovan (Acta Polytechnica, 2024)
Vehicle mobility is an increasingly important issue today, even in the military field. Mobility depends on the condition of the vehicle, the route and, of course, the experience of the driver. Vehicle failures and damage are very common in military operations. It is therefore important to find out how these failures and damage can affect mobility. One of the essential parts of a vehicle is the braking system. The authors therefore decided to investigate what is the effect of a malfunctioning brake system on emergency braking behaviour of a special vehicle in a curvilinear movement. Simulation tests were performed based on an experimentally validated model. The tests were performed with a wheeled vehicle on three different surfaces: concrete, wet asphalt, and ice. The experimental conditions were given as follows – the braking process was considered for a braking system with ABS on and off and for two states of braking system sufficiency (8 braked wheels or 4 rear braked wheels). These tests allowed us to analyse the effect of the extent of the damage on safety, in this case the stopping of the vehicle on a specified curved route. The results of braking and stability on different surfaces and under given conditions are evaluated and described in this paper. On the basis of the results, it is possible to prepare training programmes (scenarios) for drivers of special vehicles for the purpose of driving techniques in critical situations.